The Transformation of the Teacher’s Role in Creating a Social Environment that Supports Character Education - Jufri Agus; Farisatma (Jurnal Wawasan Sarjana, 2025)
This study examines the transformation of teachers’ roles in creating a social environment for character education in elementary schools, highlighting the shift from an instructional model to an ecosystemic approach. The introduction emphasizes the importance of teachers not only as transmitters of values but also as role models and architects of classroom culture who foster students’ moral growth. The main objective of this research is to analyze the multiple roles of teachers in shaping character, as well as to identify challenges and opportunities in sustaining effective character education. The study employs a qualitative descriptive method, drawing on literature reviews and recent empirical findings from case studies in Indonesian elementary schools. Data sources include previous research conducted, which provide insights into teacher practices, classroom management, and systemic constraints. The findings reveal that teachers play five complementary roles in character formation: educator, demonstrator, classroom manager, motivator, and evaluator. These roles contribute significantly to building an inclusive and value-based classroom atmosphere that enhances students’ politeness, responsibility, and social care. However, challenges remain in terms of administrative pressures, lack of character-based training, and limited institutional support. In conclusion, the study underscores that teacher transformation in character education requires pedagogical, social, and reflective capacities, as well as strong collaboration among schools, families, and communities to ensure systemic and sustainable outcomes.